PERANCANGAN HOTEL RESORT DI PANTAI WIDURI PEMALANG JAWA TENGAH - Chairul Mustakim; Karya Subagya (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Tourism is an industrial sector that has been approved and promoted since the beginning of the Government of Indonesia, with the aim of bringing in foreign exchange and introducing the State of Indonesia to foreign countries through the tourism sector. One of the famous tourism objects in Pemalang is Widuri Beach. The beach that offers affordable tourism for the surrounding community. To meet the needs of tourism during the tour in need of development of the thistle beach tourism area, especially its 5-star resort hotel (five). Development planning with the concept of tropical architecture based on proliferation in Indonesia, especially Pemalang Thistle Coastal. Separation of climates that arise such as solar heat, air temperature, rainfall, humidity.